Switching Therapy from Intravenous Landiolol to Transdermal Bisoprolol in a Patient with Thyroid Storm Complicated by Decompensated Heart Failure and Gastrointestinal Dysfunction - Godo, Shigeo (Intern Med, 2017)
Thyroid storm is a life-threatening disorder that remains a therapeutic challenge. Although β-blockers are the mainstay for treatment, their use can be challenging in cases complicated by rapid atrial fibrillation and decompensated heart failure. We present a case of thyroid storm-associated atrial fibrillation and decompensated heart failure complicated by gastrointestinal dysfunction secondary to diffuse peritonitis that was successfully managed by a switching therapy, in which the continuous intravenous administration of landiolol was changed to bisoprolol via transdermal patch, in the acute phase treatment. This switching therapy may offer a promising therapeutic option for this potentially lethal disorder.